2017
DOI: 10.1111/jopy.12302
|View full text |Cite
|
Sign up to set email alerts
|

How Likable Are Personality Disorder and General Personality Traits to Those Who Possess Them?

Abstract: These findings have implications for the ways that individuals with personality pathology perceive the people around them, which may in turn impact their expectations and behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
5
28
0
Order By: Relevance
“…Furthermore, individuals higher in trait narcissism and trait entitlement reported more subjectively positive evaluations of those traits. Such findings are generally consistent with prior literature [45,46] noting that narcissistic individuals tend to be more favorably inclined toward narcissistic traits, particularly in abstract exercises (such as rating opinions of traits).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, individuals higher in trait narcissism and trait entitlement reported more subjectively positive evaluations of those traits. Such findings are generally consistent with prior literature [45,46] noting that narcissistic individuals tend to be more favorably inclined toward narcissistic traits, particularly in abstract exercises (such as rating opinions of traits).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are supported by a recent body of research showing that individuals high in narcissistic tendencies tend to endorse generally positive attitudes toward narcissistic traits such as arrogance and boastfulness [44] and even antagonism [45]. Of note, these positive attitudes toward narcissistic traits are often more theoretical than practical [46].…”
Section: Introductionmentioning
confidence: 64%
“…Other examples are studies showing that individual differences in trait facets are relatively stable across periods of 2 weeks [57, 235], 4 months [285], and more than 1 year [286]. Further issues that have been addressed include measurement invariance or item bias due to age [287,288], gender [217,289], and clinical status [290]; response styles in PID-5 self-reports [154,155,291,292]; heritability and familial aggregation of maladaptive traits [39,289,[293][294][295]; and perceived likability, impairment, functionality, as well as desire and ability for change of maladaptive traits [68,158,[296][297][298].…”
Section: Further Issuesmentioning
confidence: 99%
“…Virtually all psychological research points to homophily ("like attracts like") as a general principle for mate preferences, although this principle appears to hold more strongly for hypothetically expressed than for actual preferences (Finkel, Eastwick, Karney, Reis, & Sprecher, 2012). Recent studies of individuals in committed relationships (Kardum, Hudek-Knezevic, Schmitt, & Covic, 2017), including married couples (Weiss etal., 2018), have revealed a small to medium association between partners' overall psychopathic traits, raising the possibility that the individuals who report the most attraction to prospective psychopathic partners are those with marked psychopathic traits themselves (for related evidence, see also Jonason, Valentine, Li, & Harbeson, 2011;Lamkin, Maples-Keller, & Miller, 2018;Sleep etal., 2017). Another study demonstrated that psychopathic females preferred males with high levels of Dark Triad traits (i.e., an amalgam of Machiavellianism, narcissism, and psychopathy; Paulhus & Williams, 2002) and found them more physically attractive, desirable for a casual sexual encounter, and even more suitable for marriage (Jonason, Lyons, & Blanchard, 2015).…”
Section: Psychopathy and Interpersonal Attractionmentioning
confidence: 99%